Formation of composite board by using HDPE and sawdust/rice husk with addition of maleic anhydride as coupling agent: article / Mohamad Noor Hadman Adam, Farid Mulana - Adam, Mohamad Noor Hadman; Mulana, Farid (2018)
In this study, composites were prepared by using two main ingredients; that are high density polyethylene (HDPE) as the matrix and mixture of rice husk and sawdust as the filler. The composites were divided into two types; composites which contain coupling agent, and the composites that did not containing coupling agent. The coupling agent used in this study is maleic anhydride (MA). The aim of this study was basically to prepare the two types of composites and to know the effect of addition of coupling agent and effect of different ratio of matrix and filler toward mechanical properties of produced composites. For this study, composites were prepared at 170°C with different ratio of matrix and filler [1]. The composites was tested with several tests; mechanical properties of the prepared composites. The bending strength of the composite was increasing with addition of coupling agent MA and also increased as the percentage of filler increased. As for the tensile strength, the addition of coupling agent lowers the tensile strength. However, there are slight inconsistencies at 40% filler. This inconsistency may due to the presence of air bubble in the composites.